Evaluasi Efektivitas Fungsi Penyidik dalam Pengungkapan Tindak Pidana Narkotika di Polrestabes Makassar (LEGAL DIALOGICA, 2026)
Abstract: This study aims to analyze the effectiveness of the investigator's function in resolving narcotics criminal cases at the Makassar Metropolitan Police (Polrestabes Makassar), as well as to examine the inhibiting factors affecting the implementation of such function. The research method used is empirical legal research with a sociological-juridical approach. Data were collected through in-depth interviews with narcotics investigators at Polrestabes Makassar, document studies of case files, and library research on relevant laws and regulations, including Law Number 35 of 2009 on Narcotics, Law Number 8 of 1981 on Criminal Procedure Law (KUHAP), and Law Number 2 of 2002 on the National Police. Data were analyzed qualitatively. Results indicate that normatively, investigator functions have been implemented in accordance with statutory provisions, covering the stages of investigation, arrest, detention, search, seizure, to submission of case files to the public prosecutor. However, several obstacles remain, including limited human resources, inadequate facilities and infrastructure, complexity of narcotics distribution networks, and the community's legal culture. Efforts to improve effectiveness include enhancing investigator capacity through training, optimizing inter- agency coordination, and strengthening investigative support facilities. This study recommends strengthening investigator professionalism and improving legal education in the community to support more effective narcotics crime enforcement.Abstrak: Penelitian ini bertujuan menganalisis efektivitas pelaksanaan fungsi penyidik dalam penyelesaian kasus tindak pidana narkotika pada Kepolisian Resor Kota Besar (Polrestabes) Makassar, serta mengkaji faktor-faktor yang menghambat pelaksanaannya. Metode yang digunakan adalah penelitian hukum empiris dengan pendekatan yuridis sosiologis melalui wawancara mendalam dengan penyidik narkotika Polrestabes Makassar, studi dokumentasi berkas perkara, dan studi kepustakaan terhadap peraturan perundang-undangan yang relevan, meliputi UU No. 35 Tahun 2009 tentang Narkotika, KUHAP, dan UU No. 2 Tahun 2002 tentang Kepolisian. Data dianalisis secara kualitatif. Hasil penelitian menunjukkan bahwa secara normatif fungsi penyidik telah dilaksanakan sesuai ketentuan peraturan perundang-undangan, mulai dari tahap penyelidikan, penangkapan, penahanan, penggeledahan,  penyitaan, hingga pelimpahan berkas perkara. Namun demikian, masih terdapat beberapa kendala yang mempengaruhi efektivitas penyidikan, antara lain keterbatasan sumber daya manusia, sarana dan prasarana, kompleksitas jaringan peredaran narkotika, serta faktor budaya hukum masyarakat. Upaya peningkatan efektivitas dilakukan melalui pelatihan kapasitas penyidik, optimalisasi koordinasi antarlembaga, dan penguatan sarana pendukung penyidikan.